"Not Just Right Experiences" are specific to obsessive–compulsive disorder: Further evidence from Italian clinical samples. (April 2015) - Sica, Claudio; Bottesi, Gioia; Orsucci, Antonella; Pieraccioli, Caterina; Sighinolfi, Cecilia; Ghisi, Marta
Highlights: NJREs may be considered a vulnerability marker for OCD. NJREs were investigated in OCD and OCD spectrum disorders. OCDs scored higher than Pathological Gambling or Eating disorders group on NJREs. NJREs appear somewhat specific to OCD. Abstract: Not Just Right Experiences (NJREs) are considered to be a perceptually tinged phenomenon mainly related to obsessive–compulsive disorder (OCD). The evidence of an association between NJREs and OCD or OC symptoms have been accumulating in the last few years, whereas there is a paucity of studies about the role of this construct in other clinical conditions considered part of the "OCD spectrum". In the current study, the NJRE-Q-R Severity scale (a well-validated measure of NJREs) was administered to 41 patients with OCD, 53 with hair-pulling disorder (HPD), 38 with gambling disorder (GD) and 43 with eating disorders (ED) along with measures of OC symptoms and general distress. In each group, NJREs were consistently associated with OC symptoms; moreover, the pattern of associations appeared coherent with the main clinical features of each disorder. The OCD group reported higher levels of NJREs severity than GD and ED, whereas there were no differences between the OCD and HPD groups. However, HPD patients did not have higher scores of NJREs severity than GD and ED counterparts. NJREs appear to be specific to OCD, but further study is needed to establish the role of this construct in OCD-related disorders.